Analytical prediction of stability lobes in high-speed milling and their application to micromilling. (23rd January 2008) - Lakshmi, L. Samrajya; Vasu, V.; Krishna, Prasad; Rao, B. Nageswara; Rakesh, S.
The rotational speeds in high-speed machining and mechanical micromachining are very high. At such high speeds, machine vibrations play an important role in the stability of the machining process. Stable-machining process is critical in maintaining surface and product quality. An important analytical tool that has been developed to aid in the selection of stable cutting parameters is the stability lobe diagram. In this paper, an algorithm was developed for the construction of stability lobe diagram. A stability lobe diagram was constructed for both high-speed milling and micromilling using the same algorithm. The algorithm was found to be satisfactory for both high-speed milling and micromilling.